Handbook of wirless networks and Mobile Computing. - Stoimenovic, Ivan (India : Wiley India, 2006)
This book provides detailed practical coverage of an array of key topics, including cellular networks, channel assignment, queuing, routing, power optimization, and much more. It covers wireless networks and mobile computing with an emphasis on computer science and system considerations rather than devices. It offers detailed, practical discussion of topics such as cellular networks, channel assignment, queuing, power optimization, and more.
Handoff in Wireless Mobile Networks -- Location Management in Cellular Networks -- Heuristics for Solving Fixed-Channel Assignment Problems -- Channel Assignment and Graph Multicoloring -- Channel Assignment and Graph Labeling -- Wireless Media Access Control -- Traffic Integration in Personal, Local, and Geographical Wireless Networks -- Fair Scheduling in Wireless Packet Data Networks (T Nandagopal & X Gao) -- Randomized Initialization protocols for Radio Networks (K Nakano & S Olariu) -- Leader Election Protocols for Radio Networks (K Nakano & S Olariu) -- Data Broadcast (J Xu, et. al) -- Ensemble Planning for Digital Audio Broadcasting (A Gräf & T McKenney) -- Transport over Wireless Networks (H Hsieh & R Sivakumar) -- Security and Fraud Detection in Mobile and Wireless Networks (A Boukerche) -- Mobile Ad Hoc Networks (S Giordano) -- Broadcast Scheduling for TDMA in Wireless Multihop Networks (E Lloyd) -- Mobile Ad Hoc Networks and Routing Protocols (Y Tseng, et. al) -- Routing with Guaranteed Delivery in Geometric and Wireless Networks (J Urrutia) -- Power Optimization in Routing Protocols for Wireless and Mobile Networks (S Lindsey, et. al) -- Dominating-Set-Based Routing in Ad Hoc Wireless Networks (J Wu) -- Location Updates for Efficient Routing in Ad Hoc Networks (I Stojmenovi) -- Topological Design, Routing, and Handover in Satellite Networks (A Ferreira, et. al) -- Multicasting: From Fixed Networks to Ad Hoc Networks (T Kunz) -- Broadcasting in Radio Networks (A Pelc) -- Mobile IP Protocols (C Douligeris & T Vasilakos) -- Data Management in Wireless Mobile Environments (S Gupta & P Srimani) -- Mobile, Distributed and Pervasive Computing (M Barbeau) -- Indoor Wireless Environments (L Ramachandran)
includes index.
1
Keywords: Wireless Mobile Networks; Graph Multicoloring; Channel Assignment; Graph Labeling; Wireless Media Access Control